Peran Kepemimpinan Guru Sekolah Minggu Bagi Pertumbuhan Spiritualitas Generasi Z Pada Era Disrupsi - Ricky Mallisa' (KINAA: Jurnal Kepemimpinan Kristen dan Pemberdayaan Jemaat, 2020)
Abstract: The purposes of this research is to analyze the leadership role of Sunday school teachers for generation z in the era of disruption. Disruption is a change in the human life system caused by the development of technological science. As a result, most human activities in the 21st century are assisted by a modern. In addition, the era of disruption was marked by the ease of access. This is an opportunity to do various activities quickly. The presence of opportunities for quick access also has an impact on the lives of Generation Z. But it makes it possible for easy access to pornographic sites that would adversely affect the Z generation and its spiritual growth. Related to that, the leadership role of the Sunday school teacher must guide the z generation in a better direction. So that, the research method used in this research is descriptive qualitative. The approach used in literature research. After that, it is described in a description. Regarding the leadership role of Sunday school teachers for generation z in the era of disruption, the findings in this study are (1) Building spirituality for generation z. (2) Educational approach. That is meant is the role of school teacher leadership to provide education oriented to the growth of Christ's character. (3) The principle of benefits approach that must be utilized for ministry, discipleship, and in the mission of the church. (4) Schoolteacher leadership is characterized by a role model for generation Z. In providing exemplary to z generation is grow in faith in the midst namely digital sophistication in the Era of Disruption.   Keywords: Disruptive, spirituality, Leadership, Z Generation.   Abstrak: Tujuan penelitian adalah untuk mengkaji peran kepemimpinan guru sekolah minggu terhadap generasi Z di era disrupsi. Disrupsi adalah perubahan sistem kehidupan manusia yang disebabkan oleh berkembangnya ilmu teknologi. Akibatnya sebagian besar aktivitas manusia di abad ke-21 ini dibantu oleh kehadiran digital yang modern. Selain itu, Era Disrupsi ditandai dengan adanya kemudahan dalam mengakses. Hadirnya peluang akses yang cepat juga berdampak bagi kehidupan generasi Z. Namun memungkinkan peluang akan mudahnya membuka situs pornografi yang berdampak buruk bagi generasi Z dan pertumbuhan spiritualitasnya. Terkait itu, peran kepemimpinan guru sekolah minggu harus membimbing generasi Z ke arah yang lebih baik. Maka metode penelitian yang digunakan adalah kualitatif deskriptif. Pendekatan yang digunakan adalah literature research. Setelah itu diuraikan secara deskripsi. Terkait peran kepemimpinan guru sekolah minggu bagi generasi Z di era disrupsi, maka temuan-temuan dalam penelitian ini adalah (1) Membangun spiritualitas bagi generasi Z. (2) Melakukan pendekatan secara edukatif. Artinya peranan kepemimpinan guru sekolah memberikan pendidikan yang berorientasi pada pertumbuhan karakter Kristus. (3) Pendekatan asas manfaat yang harus dimanfaatkan untuk pelayanan, pemuridan, dan dalam misi gereja. (4) Kepemimpinan guru sekolah minggu ditandai dengan role model. Artinya memberikan keteladanan bagi generasi Z untuk semakin bertumbuh dalam iman di tengah kecanggihan digital di Era Disrupsi.   Kata kunci: Disrupsi, Spiritualitas, kepemimpinan, Generasi Z